Barriers to Engaging with Reconciliation in Canadian Education: Confusing Colonial and Western Knowledge - Louie, Dustin William (Canadian Journal of Education / Revue canadienne de l'éducation, 2024)
In this article, I examine truths and misunderstandings of colonization. An interrogation of the conflation between colonial and Western practices is explored through established literature and in practical examples of relationships to time, the Indian Act, and the term “Settler.” By first establishing accessible and shared definitions of reconciliation and colonization, common misconceptions and predictable pitfalls in Indigenous movements can be resolved. By attending to the confusion of terms the circle can be expanded ever so slightly to welcome more allies into the movement. Intentionally deceptive narratives position the work of reconciliation, or any social justice movement, as being anti-White and divisive. In the pursuit of equity and healing, it is essential to maintain the core values of care and dignity in methods of emancipation and resist succumbing to colonial tactics of delegitimizing any knowledge system, even those of our oppressors.